PENGARUH KEPEMILIKAN ASING DAN FAKTOR LAINNYA TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Isna Mulansari; Ponny Harsanti; Zamrud Mirah Delima (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This study aims to examine the effect of foreign ownership,institutional ownership, leverage, and the size of the board ofdirectors on the disclosure of corporate social responsibility.The population used is mining companies listed on the IndonesiaStock Exchange (IDX) for 2016-2020 with a sample that has beenselected using the purposive sampling method. The total sampleanalyzed was 61 companies using multiple linear regressionanalysis with the help of SPSS 25. The results showed that the sizeof the board of directors has a positive effect on the disclosure ofcorporate social responsibility. Foreign ownership, institutionalownership, and leverage have no effect on the disclosure ofcorporate social responsibility.